Molecular Simulation of Fundamental Processes in Nanoparticle - Polymer - Nanoparticle Systems Under Tensile Load - Zahn, Dirk (International Journal of Materials, Mechanics and Manufacturing, 2013)
We demonstrate molecular modeling of polymer (polyacrylate) association to ZnO nanoparticles by means of a recently developed molecule-by-molecule association approach. Upon multiple acrylate association steps, potential sites for connecting ZnO particles are elaborated and explored under tensile loading from molecular dynamics simulation. This offers molecular level insights into processes that account for elastic and plastic deformation, creep and self-healing in ZnO-polymer composite materials.
EAM Import::2019-03-12